2019
DOI: 10.1021/acsami.9b06346
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electrocatalytic Oxygen Reduction Reaction Activity of Pt–Co Nanocrystals by Cobalt Concentration with Atomic-Scale Understanding

Abstract: The development of a suitable catalyst for the oxygen reduction reaction (ORR), the cathode reaction of proton exchange membrane fuel cells (PEMFC), is necessary to push this technology toward widespread adoption. There have been substantial efforts to utilize bimetallic Pt−M alloys that adopt the ordered face-centered tetragonal (L1 0 ) phase in order to reduce the usage of precious metal, enhance the ORR performance, and improve catalyst stability. In this work, monodisperse Pt−Co nanocrystals (NCs) with wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 64 publications
1
55
1
Order By: Relevance
“…For instance, it has been reported that a mixed solution of Co and Pt is preferable for high activity with the ORR. Some studies have focused on Pt 3 Co alloys, while others indicate that PtCo is an even more efficient catalyst for these same reactions. As another example, synergy between Co and Pt has been observed for the conversion of ethane and CO 2 into syngas . In that study, CoPt particles doubled the conversion of ethane and CO 2 , compared to its monometallic constituents.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, it has been reported that a mixed solution of Co and Pt is preferable for high activity with the ORR. Some studies have focused on Pt 3 Co alloys, while others indicate that PtCo is an even more efficient catalyst for these same reactions. As another example, synergy between Co and Pt has been observed for the conversion of ethane and CO 2 into syngas . In that study, CoPt particles doubled the conversion of ethane and CO 2 , compared to its monometallic constituents.…”
mentioning
confidence: 94%
“…For instance, segregation of Co and Pt can be responsible for reduced catalytic properties after cycling. , Changes in the valence state during reaction impacts the electronic configuration at the sample’s surface and ultimately affects absorption and desorption energies for gas molecules . It is known that freshly synthesized Co–Pt particles can have compositional heterogeneities, with partial segregation of Co and Pt. Exposure of the Co–Pt system to H 2 or other nonoxidative atmospheres at elevated temperatures has been shown to improve the mixing of Co and Pt, and can lead to the formation of an intermetallic solution. ,, However, it is not clear whether some Co remains segregated and oxidized during and after annealing. This point is important because incomplete reduction and mixing of Co and Pt will impact the catalytic properties for HER, ORR, or gas-phase reactions.…”
mentioning
confidence: 99%
“…However, also the arrangement in which the atoms are assembled is crucial; gas-and thermally-induced metal redistribution can have a large impact on the catalytic performance [12,13,14]. Thanks to recent advances in ma-terial science, it is now possible to synthesize bimetallic nanoparticles with precisely defined atomic arrangements such as single-atom alloys [15,16], intermetallic structures [17] and core-shell materials [18,19]. Yet, the number of systematic studies linking the metal distribution to the performance of bimetallic catalysts is limited [12,13,14].…”
Section: Extending the Toolbox From Mono-to Bimetallic Catalysts Is Kmentioning
confidence: 99%
“…To reduce Pt usage, Pt-M alloys (M: Fe, [11][12][13] Ni, [14][15][16][17][18][19] Co, [20][21][22][23] Cu, [24][25][26][27] etc.) that are random mixtures of Pt and M atoms have been extensively explored.…”
Section: Introductionmentioning
confidence: 99%